2016
DOI: 10.1111/glob.12135
|View full text |Cite
|
Sign up to set email alerts
|

Navigating transnational childcare relationships: migrant parents and their children's caregivers in the origin country

Abstract: In this article, we investigate the daily work entailed in maintaining informal transnational childcare relationships between migrant parents and the children's kin or non‐kin caregivers in the country of origin. By applying the concept of ‘kin work’, we seek to understand how work is performed within transnational care relationships. Using a simultaneous matched sample methodology that gives equal weight to data on both sides of the transnational relationship, a team of researchers collected ethnographic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 37 publications
2
71
0
3
Order By: Relevance
“…The African context may differ because of the prevalent norms around family life characterized by social parenthood and child fostering, making it common for children to change residency and be raised by people other than their biological parents, irrespective of parental migration status (Radcliffe-Brown & Forde, 1950). This may contribute to the fact that Ghanaian children do not necessarily feel underprivileged if they do not live with their parents (Poeze et al, 2017) as has been found in other contexts (Cortes, 2015;Parreñas, 2005). Finally, an important distinguishing factor is that few studies on migration and child well-being ask children to evaluate their well-being and instead rely on the assessments of adults such as parents, other caregivers, or teachers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The African context may differ because of the prevalent norms around family life characterized by social parenthood and child fostering, making it common for children to change residency and be raised by people other than their biological parents, irrespective of parental migration status (Radcliffe-Brown & Forde, 1950). This may contribute to the fact that Ghanaian children do not necessarily feel underprivileged if they do not live with their parents (Poeze et al, 2017) as has been found in other contexts (Cortes, 2015;Parreñas, 2005). Finally, an important distinguishing factor is that few studies on migration and child well-being ask children to evaluate their well-being and instead rely on the assessments of adults such as parents, other caregivers, or teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of kin to provide care to children is seen as an enabling factor allowing African parents to migrate alone for work (Madhavan et al, 2012). Conversely, when migrant parents have difficulties finding a suitable caregiver in the local network of people, then tensions may arise within the transnational family (Poeze, Dankyi, & Mazzucato, 2017). The quality of care provided by the caregiver is also of relevance and is expected to be higher when the caregiver is one of the parents of the child or a close family kin member (Schmalzbauer, 2004).…”
Section: Migration and The Well-being Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…The risks to children include poor or decreased educational attainment, deviant or anti-social behaviour, a 'happiness deficit' and emotional problems. Other people in the 'care triangle' are also vulnerable because of the strain on resources and emotional challenges (Graham et al 2012;Poeze et al 2016).…”
Section: A Resilience Approach To Transnational Family Studiesmentioning
confidence: 99%
“…More recent studies on the impacts of ICTs on these relationships have extended this theme, but they have found that the technologies create redemptive effects, enabling both intensified intimacies and surveillance practices. This article complements work on the quality of intimacy within longdistance parenting relationships and relationships between migrant parents and the children's caregivers (Poeze et al 2016) through exploring the more public aspects of SNS. Social media make parenting relationships with sent-home and left-behind children public, and SNS thus become part of the assemblage through which migration and childhoods are governed.…”
mentioning
confidence: 95%